A study on the influence of hiv infection in pulmonary tuberculosis patients on the se condary transmission of pljlmonary tuberculosis to household contacts - Wan Mohammad , Wan Mohd Zahiruddin (2001)
Introduction: The Human Immunodefiency Virus (HIV) epidemic has had a profound influence on the transmission of tuberculosis (TB). The potential for HIV -associated TB cases to transmit M.tuberculosis and to produce a secondary increase in TB morbidity is unknown. Objectives: To compare the prevalence of M.tuberculosis infection among household contacts of HIV-positive and HIV-negative pulmonary TB (PTB) patients, and to identify potential variables that associated with the transmission. Materials and Methods: A cross-sectional study was carried out to review records of tuberculin (Mantoux) tests administered during routine contact investigations at the Chest Clinic, Kota Bharu Hospital, Kelantan from 1999 through 2000. HIV status of patients was based on the result of ELISA tests while information on household contacts were recorded during house visit. Results: One hundred and sixty eight contacts to 67 HIV -negative patients and 62 contacts to 22 cases of HIV -positive PTB patients were included. Thirty-two percents (20/62) of contacts of HIVpositive PTB had a positive tuberculin compared with 49.4 % (83/168) of contacts to HIVnegative patients (crude Odds Ratio (OR) = 0.48 95% Confidence Interval (el) 0.26 - 0.90, p = O. 020). HIV -infected PTB patients in this study had a less severe form of pulmonary lesion without cavitations. The difference in tuberculin response among the household contacts of each group was still significant after performing multivariate logistic regression analysis to adjust for the severity of PTB and other potential variables associated with infectiousness of TB (adjusted OR = 0.43, 95% CI 0.18 - 0.95 P = 0.04). Adult contacts, crowding of house, longer duration of stay with index. cases, presence of sputum positive and cavitations on chest X-ray in index cases showed higher odds of being tuberculin positive among household contacts but the differences were not significant. Conclusion: The study has shown that HIV -infected PTB were less infectious to their household contacts than HIVnegative patients. The study suggests that the more advanced HIV -associated immunosuppresion among the PTB index cases, the less infectious is the PTB. The transmissibility of TB may depend on the stage of HIV infection i.e patients who are immunosuppressed are less likely to cavitate and have milder pulmonary lesions, and therefore are less infectious than those patients who are at an early stage of HIV infection. The presence of HIV in the community may not necessitate a change in the current policy in the management of contacts in the general population.